2021
DOI: 10.21037/tp-21-105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different administration and dosage of dexmedetomidine in the reduction of emergence agitation in children: a meta-analysis of randomized controlled trials with sequential trial analysis

Abstract: Background: Beneficial effects of dexmedetomidine (DEX) against emergence agitation (EA) in children remain controversial. We performed a more comprehensive meta-analysis to evaluate the protective effect of different administration routes, timing, patterns, and doses of DEX on EA in children. Methods:The randomized controlled trials about DEX preventing EA in children were searched in PubMed, Cochrane Library, Embase, and Web of Sciences up to October 7, 2020. The traditional meta-analysis and subgroup analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 93 publications
3
6
0
Order By: Relevance
“…This process resembles natural sleep and awakening with anxiolytic sedative effects and without respiratory depression. Previous research [ 19 ] has demonstrated that the application of dorsal penile nerve block combined with dexmedetomidine anesthesia in pediatric circumcision features a fast onset of action, stable vital signs of patients, and less postoperative agitation, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This process resembles natural sleep and awakening with anxiolytic sedative effects and without respiratory depression. Previous research [ 19 ] has demonstrated that the application of dorsal penile nerve block combined with dexmedetomidine anesthesia in pediatric circumcision features a fast onset of action, stable vital signs of patients, and less postoperative agitation, which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also demonstrate that dexmedetomidine minimizes PONV and the need for rescue analgesia without delaying discharge from the PACU. These findings are consistent with those of earlier meta-analyses [ 33 34 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the dexmedetomidine group, all children were calm post-extubation and had significantly lower RASS and CHEOPS scores with no incidence of emergence agitation. Our findings support the high-quality evidence from a recent meta-analysis by Zhang et al [ 33 ], which demonstrated the benefits of maintenance infusion of dexmedetomidine on emergence agitation in children. Our findings also demonstrate that dexmedetomidine minimizes PONV and the need for rescue analgesia without delaying discharge from the PACU.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with intravenous administration, intranasal administration of dexmedetomidine has a longer absorption process, and this results in a longer duration of action, more satisfactory sedation and less postoperative agitation 8,12 . Several studies have reported intranasal dexmedetomidine to be associated with a decrease in the incidence of emergence agitation after paediatric inhalational anaesthesia, but various doses were used and the optimal dose was uncertain 13–15 . Yao et al 14 reported the incidence of emergence agitation as 16.7 and 3.3% with 1 and 2 μg kg −1 intranasal dexmedetomidine, respectively, in children aged 3 to 7 years after sevoflurane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%